2023
DOI: 10.3390/molecules28186745
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Biosynthesis of Non-Canonical Amino Acids (ncAAs) and the Methods of ncAAs Incorporation into Proteins

Liang Chen,
Xiulan Xin,
Yuning Zhang
et al.

Abstract: The functional pool of canonical amino acids (cAAs) has been enriched through the emergence of non-canonical amino acids (ncAAs). NcAAs play a crucial role in the production of various pharmaceuticals. The biosynthesis of ncAAs has emerged as an alternative to traditional chemical synthesis due to its environmental friendliness and high efficiency. The breakthrough genetic code expansion (GCE) technique developed in recent years has allowed the incorporation of ncAAs into target proteins, giving them special f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 140 publications
(157 reference statements)
0
7
0
Order By: Relevance
“…Currently, the amber codon (UAG) is the most frequently used new genetic code, because it is the least used termination codon in E. coli cells (ca. 7%). , Below we only briefly discuss its working principle and direct interested readers to several recent reviews. …”
Section: Methods Of Incorporationmentioning
confidence: 99%
“…Currently, the amber codon (UAG) is the most frequently used new genetic code, because it is the least used termination codon in E. coli cells (ca. 7%). , Below we only briefly discuss its working principle and direct interested readers to several recent reviews. …”
Section: Methods Of Incorporationmentioning
confidence: 99%
“…The correctly aminoacylated tRNAcAA (blue with green sphere) and the misacylated tRNA (red with orange star) are processed by the ribosome to give a globally modified protein. conducive for precise control of protein modification, 11 and depending on the ncAA, it has been shown to have lower incorporation efficiencies than SSI. 19 3.2.1.…”
Section: Residue-specific Incorporation (Rsi)mentioning
confidence: 99%
“…Obtaining enantiomerically pure ncAAs in the quantities required for large-scale applications continues to pose a challenge, though the emerging biocatalytic production methods are proving to be suitable alternatives in terms of cost and sustainability. 11,35,80,81 Biocatalytic synthesis also offers the opportunity of coupling the production of the ncAAs with their incorporation into proteins. 80−83 Schipp et al have demonstrated this by reconfiguring the methionine biosynthetic pathway in an E. coli strain to create a trans-sulfuration pathway for the in-cell production and incorporation of L-azidohomoalanine (Aha).…”
Section: Residue-specific Incorporation (Rsi)mentioning
confidence: 99%
See 2 more Smart Citations